"Wrong Majors Phenomenon": a Challenge for Indonesia in Molding Globally Competent Human Resources to Encounter Demographic Dividend - Rizaldy Ali (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2018)
The growth of youth population has now become a strategic consideration of global trends predicted by 2030. In many parts of the world, the growth of youth population is increasingly uncontrolled. According to the Central Agency on Statistics, it revealed that Indonesia's population is dominated by a productive age group that is between 15-64 years old. This condition shows that Indonesia is moving into an era of demographic dividend. However, the fact that the human development index of Indonesia is too low; Indonesia ranked 110 out of 188 countries in the world and with massive numbers of academic unemployment, as if showing the unpreparedness of Indonesia in facing demographic dividend. This paper, attempts to highlight upon; the immense impact of mistaking majors to the human resource competence. Examine the key factors of wrong majors' phenomenon, and how do implications arise when students are incorrectly selected. The research used a descriptive method; source data ascribed to field research; and study of literature. Through this research, the most striking findings are: the key factors that trigger wrong majors' phenomenon that is caused by the influence of significant person statistics, low passing grade becoming their consideration to be accepted in college; they didn’t gain any intensive preparation for going to college; the existence of consciousness upon the demands of experts, so that they preferred majors based on what the market needs not relying on their interest; and also the fears for not doing anything after graduating from high school. Mistaking majors implies towards the psychic of the college student; such as, highly vulnerable to being stressed because they are not able to adjust to the learning process.